Potential of phage depolymerase for the treatment of bacterial biofilms - Zhimin Guo; Mengmeng Liu; Dan Zhang (Virulence)
Resistance of bacteria to antibiotics is a major concern in medicine and veterinary science. The bacterial biofilm structures not only prevent the penetration of drugs into cells within the biofilm’s interior but also aid in evasion of the host immune system. Hence, there is an urgent need to develop novel therapeutic approaches against bacterial biofilms. One potential strategy to counter biofilms is to use phage depolymerases that degrade the matrix structure of the bacteria and enable access to bacterial cells. This review mainly discusses the methods by which phage depolymerases enhance the efficacy of the human immune system and the therapeutic applications of some phage depolymerases, such as single phage depolymerase application, combined therapy with phage depolymerase and antibiotics, and phage depolymerase cocktails, for treating bacterial biofilms. This review also summarizes the relationship between bacterial biofilms and antibiotic resistance.